2020
DOI: 10.1186/s13567-020-00760-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of siRNA silencing on the susceptibility of the fish cell line CHSE-214 to Yersinia ruckeri

Abstract: Yersinia ruckeri is a facultative intracellular enterobacterium mostly known as the causative agent of enteric redmouth disease in salmonid fish. In the present study, we applied RNA inhibition to silence twenty pre-selected genes on the genome of a fish cell line (CHSE-214) followed by a gentamicin assay to quantify the effect of silencing on the cells' susceptibility to infection and found that silencing of 18 out of 20 genes significantly reduced the number of Y. ruckeri recovered. These findings improve ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Some bacterial pathogens like Mycobacterium tuberculosis (MTB), Listeria monocytogenes , Mycobacterium fortuitum , S. typhimurium , and Yersiniaceae need host cell facilities for entry and invasion ( Agaisse et al, 2005 ). Inactivating the invasion related genes like SEC22A, Rab1B, and VPS33B by siRNA can prevent bacterial cell entrance to the host cells ( Menanteau-Ledouble et al, 2020 ). In our recent in vitro study, we designed specific siRNA against urease B subunit (ureB) and cytotoxin-associated gene A (CagA) genes from Helicobacter pylori .…”
Section: Therapeutics Sirna For Microbial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some bacterial pathogens like Mycobacterium tuberculosis (MTB), Listeria monocytogenes , Mycobacterium fortuitum , S. typhimurium , and Yersiniaceae need host cell facilities for entry and invasion ( Agaisse et al, 2005 ). Inactivating the invasion related genes like SEC22A, Rab1B, and VPS33B by siRNA can prevent bacterial cell entrance to the host cells ( Menanteau-Ledouble et al, 2020 ). In our recent in vitro study, we designed specific siRNA against urease B subunit (ureB) and cytotoxin-associated gene A (CagA) genes from Helicobacter pylori .…”
Section: Therapeutics Sirna For Microbial Infectionsmentioning
confidence: 99%
“…Menanteau-Ledouble et al, reported that siRNA targets and silence zipper and trigger processes related to genes in Yersinia ruckeri , the causative agent of enteric red mouth in fish. They reported that Rab1A , myotubularin , Lama2 , and Rac1 were more strongly silenced by siRNA ( Criss and Casanova, 2003 ; Menanteau-Ledouble et al, 2020 ). Silencing of Caveolin-2 as a host gene involved in the invasion of Pseudomonas aeruginosa by siRNAs leads to the reduction of bacterial pathogenesis ( Zaas et al, 2005 ).…”
Section: Therapeutics Sirna For Microbial Infectionsmentioning
confidence: 99%
“…The role of RNA interference (RNAi) has shown significant antiviral activity against many viruses as well as other pathogens and diseases by using short interfering RNAs (siRNAs) and micro-RNA (miRNAs). Long noncoding RNAs (lncRNAs) against cancers ( Mahmoodi et al, 2019 , Hattab et al, 2021 ), bacterial infections ( Menanteau-Ledouble et al 2020 ) fungal infections (Bruch et al 2022; Wang et al 2022 ), parasitic infections ( Somarathne et al 2018 ; Portet 2021), viral infections (Levanova et al 2018). Several potential RNA interference-based (RNAi) drugs have been recently reported ( Setten et al2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotide-based antiviral therapies using siRNA, shRNA, and miRNA are being evaluated. Long noncoding RNAs (lncRNAs) against cancers [9,10], bacterial infections [11], fungal infections [12,13], parasitic infections [14,15], viral infections [16]. Several potential RNA interference-based (RNAi) drugs have recently been reported [17].…”
Section: Introductionmentioning
confidence: 99%